Crescimento de mudas de caré (Coffea arabica L. var. Bourbon) sob diferentes níveis de luz - Maestri, Moacyr; Ribeiro Gomes, Fábio (Revista Ceres, 2024)
Seedlings from Coffea arabica, var. bourbon, transplanted at the “butterfly” stage (cotiledonary leaves fully open), and grown in straw pots_under four levels of sunlight, namely 100 per cent (open sun), and 75, 50 and 25 per cent, as transmitted by lath shades, gave the following results, 140 days aiter transplanting: